2020
DOI: 10.24912/jmbk.v4i2.7510
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perceived Value, Brand Image, dan Trust Terhadap Loyalitas Pelanggan

Abstract: The purpose of this research is to understand the effect of perceived value, brand image, and trust to Customers' Loyalty. The research design is based on descriptive method and the data was collected through primary data with five Likert-Scales questionaire. The samples of this research are customer who use one of the LCC flight service at least 2 times in 3 months. Convenience sampling method was used in order to gather data. Out of 200 questioners, 167 questioners were computed with SPSS to give the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…A better position of personal selling and digital marketing can improve the perceived value experienced by customers/users of the m-banking loyalty. Kelvianto (2020) stated that perceived value Creating perceived value is like giving value to the customers and ensuring that the value is higher than the value given by the competitor company. The capability to give customer value represents Perceived Value can motivate consumers to be loyal to a product, so that a high rating will increase organizational capability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better position of personal selling and digital marketing can improve the perceived value experienced by customers/users of the m-banking loyalty. Kelvianto (2020) stated that perceived value Creating perceived value is like giving value to the customers and ensuring that the value is higher than the value given by the competitor company. The capability to give customer value represents Perceived Value can motivate consumers to be loyal to a product, so that a high rating will increase organizational capability.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived Value can motivate consumers to be loyal to a product, so that a high rating will increase loyalty. (Kelvianto, 2020), found that perceived value has a positive and significant impact on consumer loyalty. Gultom et al (2016) proved that perceived value has no effect on consumer loyalty.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The customer's evaluation of what is received in comparison to what is supplied is known as perceived value. Customers are motivated to remain loyal to products or services by perceived value, which has a major positive influence on loyalty [71]. Customers' perceptions of a product are well-formed when they receive it in line with their preferences.…”
Section: Perceived Value Has a Positive Impact On Intentionmentioning
confidence: 99%
“…In research conducted by Ramadhan & Siagian (2019), it is stated that perceived value affects customer loyalty. Research conducted by Kelvianto (2020) When buying goods or services, one of the factors that customers consider is trust. Customers need to believe whether the goods or services offered by the company can answer the problems that customers have.…”
Section: P-1412-3789 Wwwjournalmabisorg E-2477-1783 50mentioning
confidence: 99%